Association of plasma arginine with breast cancer molecular subtypes in women of Liaoning province. Issue 12 (31st October 2016) - Hu, Lu; Gao, Yu; Cao, Yunfeng; Zhang, Yinxu; Xu, Minghao; Wang, Yuanyuan; Jing, Yu; Guo, Shengnan; Jing, Fangyu; Hu, Xiaodan; Zhu, Zhitu
Abstract: Arginine is one of the human nonessential amino acids critical for the growth of human cancers. The aim of this study is to investigate the variation of arginine between breast cancer (BC) patients and benign mammary gland disease (control) patients to determine its value in predicting the risk of BC. We also explore the associations between arginine levels and breast cancer subtypes. Preoperative blood samples were obtained from 267 patients (102 BC and 165 controls) in 2015. Plasma arginine values were determined for all preoperative blood samples using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) to analyse differences in arginine levels between BC patients and control patients and the correlations between arginine and clinicopathologic parameters in BC. The arginine levels of BC patients were significantly lower than those of control patients (5.96 [3.76–12.47] vs. 12.54 [7.14–24.94], P = 0.000). The area under the curve (AUC) for arginine was 0.721 (95% CI, 0.660–0.782, P  < 0.0001). The concentration of arginine was significantly different among different molecular BC subtypes ( P = 0.030). Our results suggested that plasma arginine was associated with breast cancer molecular subtypes. © 2016 IUBMB Life, 68(12):980–984, 2016